Mannose receptor-targeted MSC-derived exosomes as a high-affinity delivery platform for liver sinusoidal endothelial cells - Ji Won Lee; Jin Suk Lee; Kangchan Choi; Mi Ra Lee; Seul Ki Han; Soon Koo Baik; Yong Serk Park; Moon Young Kim (Drug Delivery and Translational Research, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Metabolomic analysis reveals stepwise metabolic adaptation to extended photoperiods in developing pea sprouts - Jong Sung Lee; Yu-Mi Shin; Ye Jin Kim; Young Jin Park; Tae Jin Kim; Sun-Hwa Ha; HanGyeol Lee; Ji-Eun Ra; Sang Un Park; Woo Duck Seo; Jae Kwang Kim (Food Chemistry, 2026)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Propylparaben-induced endoplasmic reticulum stress triggers G2/M phase cell cycle arrest and initiates caspase-3-dependent apoptosis in human lung cells - Geun-Seup Shin; Yuna Park; Ji-Young Kim; Chul-Hong Kim; Mi-Jin An; Hyun-Min Lee; Ah-Ra Jo; Jinho Kim; Yujeong Hwangbo; Jung-Woong Kim (Genes & Genomics, 2025)

Heavy metal exposure and its effects on APOC3, CFAI, and ZA2G - Nam-Eun Kim; Min Heo; Hyeongyu Shin; Ah Ra Do; Jeeyoung Kim; Hee-Gyoo Kang; Sora Mun; Hyun Ju Yoo; Mi Jeong Kim; Jung-Woong Kim; Chul-Hong Kim; Young-Seoub Hong; et al. (Journal of Hazardous Materials, 2025)

National long-term monitoring and risk assessment of various veterinary drug residues in livestock products in the Republic of Korea - Yu Ra Kim; Dahae Park; Jin Ha Sim; Hyesu Lee; Ji Young Kim; Dong-Woo Shin; Mi Ok Eom (Food Control, 2025)

Cancer therapeutic potential of hovetrichoside C from Jatropha podagrica on apoptosis of MDA-MB-231 human breast cancer cells - Dahae Lee; Seo Yoon Lee; Moon-Jin Ra; Sang-Mi Jung; Jeong-Nam Yu; Ki Sung Kang; Ki Hyun Kim (Food and Chemical Toxicology, 2024)

A new cyclin-dependent kinase-9 inhibitor A09-003 induces apoptosis in acute myeloid leukemia cells with reduction of myeloid cell leukemia sequence-1 protein - Kyoung Mi Sim; So Young Kim; Supyong Hwang; Sojung Park; Bo Ra Lee; Kyyoub Nam; SeakHee Oh; Inki Kim (Chemico-Biological Interactions, 2023)

Comparison of the cytotoxicity of bisphenol A and its analogs on human placental BeWo cells - Mi Jin Kim; Ah-Ra Jo; Ji-Young Kim; Mi-Jin An; Geun-Seup Shin; Hyun-Min Lee; Jinho Kim; Jinhong Park; Chul-Hong Kim; Jung-Woong Kim (Molecular & Cellular Toxicology, 2023)

c-Jun N-terminal kinase 1 (JNK1) phosphorylates OTX2 transcription factor that regulates early retinal development - Mi-Jin An; Hyun-Min Lee; Chul-Hong Kim; Geun-Seup Shin; Ah-Ra Jo; Ji-Young Kim; Mi Jin Kim; Jinho Kim; Jinhong Park; Yujeong Hwangbo; Jeongkyu Kim; Jung-Woong Kim (Genes & Genomics, 2023)

Application and Validation of an Ecological Quality Index, ISEP, in the Yellow Sea - Jae-Won Yoo; Yong-Woo Lee; Mi-Ra Park; Chang-Soo Kim; Sungtae Kim; Chae-Lin Lee; Su-Young Jeong; Dhongil Lim; Sung-Yong Oh (Journal of Marine Science and Engineering, 2022)
An ecological index of macrobenthic communities is an important tool for assessing the biological quality of habitats and ecosystems. We tested the performance of the inverse function of the Shannon–Wiener evenness proportion (ISEP) with data from the entire west coast of Korea, seasonally sampled from 2006 to 2008. Two validations were performed: (1) examination of the relationship between ISEP and environmental factors and (2) correspondence between the ISEP and the Pearson–Rosenberg (P-R) model for the species-abundance-biomass (SAB) patterns and taxonomical variations. The ISEP was significantly correlated with suspended solids but independent of other natural habitat conditions due to their low to moderate contamination levels. From this, ISEP performed as expected in transitional zones of low salinity and applications across habitats of various sediments. The SAB patterns and taxonomic variations along the ISEP grades showed marked similarities to the P-R model. The only departure was biomass, which increased after the normal status. The increase was interpreted as reflecting a healthier and more mature status. Taxonomic variation patterns and the taxa composition that characterized either poor or healthy status corresponded well with the P-R model. The conformity to the P-R model indicates the capability and potential applicability of the ISEP to other coastal systems.

Effect of IgG Fc-fusion and KDEL-ER retention signal on prostate-specific antigen expression in plant and its immune in mice - Chunha Shin; Kibum Kim; Yang Joo Kang; Deuk-Su Kim; Young-Jin Seo; Se Ra Park; Mi Kyung Kim; Young Koung Lee; Do-Sun Kim; Kisung Ko (Plant Biotechnology Reports, 2022)

Genetic analysis of porcine parvoviruses detected in South Korean wild boars - Gyu-Nam Park; Sok Song; Ra Mi Cha; SeEun Choe; Jihye Shin; Song-Yi Kim; Bang-Hun Hyun; Bong-Kyun Park; Dong-Jun An (Archives of Virology, 2021)

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

Clinical characteristics and outcomes of Staphylococcus aureus bacteremia from a biliary source - Eunmi Yang; Jeongsoo Lee; Hyeonji Seo; Hyemin Chung; Sang Hyun Ra; Heungsup Sung; Mi-Na Kim; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Complete genome sequence of Sphingobium sp. strain PAMC 28499 reveals a potential for degrading pectin with comparative genomics approach - So-Ra Han; Sung-Min Jang; Young Min Chi; Byeollee Kim; Sang-Hee Jung; Yung Mi Lee; Jun Uetake; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (Genes & Genomics, 2020)

Effect of Alginate Oligosaccharides on Collagen Expression in HS 27 Human Dermal Fibroblasts - Ra-Mi Park; Ji-Young Ahn; Sang Yong Kim; Ji-Hyang Wee; Yang-Hoon Kim; Jiho Min (Toxicology and Environmental Health Sciences, 2019)

Chrysophanol, an anthraquinone from AST2017-01, possesses the anti-proliferative effect through increasing p53 protein levels in human mast cells - Na-Ra Han; Hee-Yun Kim; Soonsik Kang; Mi Hye Kim; Kyoung Wan Yoon; Phil-Dong Moon; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Identification of novel mutations in the rice starch branching enzyme I gene via TILLING by sequencing - HyunJung Kim; Mi-ra Yoon; Areum Chun; Thomas H. Tai (Euphytica, 2018)

Total and Methyl Mercury Concentrations in Antarctic Toothfish (Dissostichus mawsoni): Health Risk Assessment - Minchul Yoon; Mi Ra Jo; Poong Ho Kim; Woo Seok Choi; Sang In Kang; Seok Gwan Choi; Jong Hee Lee; Hee Chung Lee; Kwang Tae Son; Jong Soo Mok (Bulletin of Environmental Contamination and Toxicology, 2018)

Isolation and characterization of a novel glycosyl hydrolase family 74 (GH74) cellulase from the black goat rumen metagenomic library - Yun-Hee Song; Kyung-Tai Lee; Jin-Young Baek; Min-Ju Kim; Mi-Ra Kwon; Young-Joo Kim; Mi-Rim Park; Haesu Ko; Jin-Sung Lee; Keun-Sung Kim (Folia Microbiologica, 2017)

Formaldehyde and heavy metal migration from rubber and metallic packaging/utensils in Korea - Su-Un Kim; Tae-Rang Kim; Eun-Soon Lee; Mi-Sun Kim; Chang-Kyu Kim; Li-Ra Kim; Gi-Young Shin (Food Additives & Contaminants Part B-Surveillance, 2015)

Relationships Between Blood Mg2+ and Energy Metabolites/Enzymes After Acute Exhaustive Swimming Exercise in Rats - Md. Mahbubur Rahman; Sei-Jin Lee; A-Reum Mun; Gareeballah Osman Adam; Ra-Mi Park; Gi-Beum Kim; Hyung-Sub Kang; Jin-Shang Kim; Shang-Jin Kim; Sung-Zoo Kim (Biological Trace Element Research, 2014)

A biochemical and physicochemical comparison of two recombinant enzymes used for enzyme replacement therapies of hunter syndrome - Yo Kyung Chung; Young Bae Sohn; Jong Mun Sohn; Jieun Lee; Mi Sun Chang; Younghee Kwun; Chi Hwa Kim; Jin Young Lee; Yeon Joo Yook; Ah-Ra Ko; Dong-Kyu Jin (Glycoconjugate Journal, 2014)

In vitro antibacterial and synergistic effect of phlorotannins isolated from edible brown seaweed Eisenia bicyclis against acne-related bacteria - Jeong-Ha Lee; Sung-Hwan Eom; Eun-Hye Lee; Yeoun-Joong Jung; Hyo-Jung Kim; Mi-Ra Jo; Kwang-Tae Son; Hee-Jung Lee; Ji Hoe Kim; Myung-Suk Lee; Young-Mog Kim (Algae, 2014)

Multiplex minisequencing screening for PTC genotype associated with bitter taste perception - Borum Sagong; Jae Woong Bae; Mee Ra Rhyu; Un-Kyung Kim; Mi-Kyung Ye (Molecular Biology Reports, 2014)

MicroRNA-205 suppresses the oral carcinoma oncogenic activity via down-regulation of Axin-2 in KB human oral cancer cell - Jae-Sung Kim; Sun-Young Park; Seul Ah Lee; Min-Gyeong Park; Sun-Kyoung Yu; Myoung-Hwa Lee; Mi-Ra Park; Su-Gwan Kim; Ji-Su Oh; Sook-Young Lee; Chun Sung Kim; Heung-Joong Kim; et al. (Molecular and Cellular Biochemistry, 2014)

Gene expression profiles of human lung epithelial cells exposed to toluene - Yu-Ri Kim; In-Kyoung Kim; Seung Ho Lee; Eun-Jung Lee; Mi Jung Pyo; Hee Ra Lee; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Toxicology and Environmental Health Sciences, 2012)

Developmental expression of plasma glutathione peroxidase during mouse organogenesis - Ki Youn Jung; In-Jeoung Baek; Jung-Min Yon; Se-Ra Lee; Mi-Ra Kim; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2011)

Environmental quality of Korean coasts as determined by modified Shannon–Wiener evenness proportion - Jae-Won Yoo; Yong-Woo Lee; Jennifer L. Ruesink; Chang-Gun Lee; Chang-Soo Kim; Mi-Ra Park; Kon-Tak Yoon; In-Seo Hwang; Jun-Ho Maeng; Rutger Rosenberg; Jae-Sang Hong (Environmental Monitoring and Assessment, 2010)

Benzyl isothiocyanate exhibits anti-inflammatory effects in murine macrophages and in mouse skin - Yeo Myeong Lee; Mi Ra Seon; Han Jin Cho; Jong-Sang Kim; Jung Han Yoon Park (Journal of Molecular Medicine, 2009)

The spatio-temporal expression pattern of cytoplasmic Cu/Zn superoxide dismutase (SOD1) mRNA during mouse embryogenesis - Jung-Min Yon; In-Jeoung Baek; Se-Ra Lee; Yan Jin; Mi-Ra Kim; Sang-Seop Nahm; Jong-Soo Kim; Byeongwoo Ahn; Beom Jun Lee; Young Won Yun; Sang-Yoon Nam (Journal of Molecular Histology, 2008)

Synaptic connections of cone bipolar cells that express the neurokinin 1 receptor in the rabbit retina - In-Beom Kim; Mi Ra Park; Tae-Hoon Kang; Hyun-Ju Kim; Eun-Jin Lee; Myung-Douk Ahn; Myung-Hoon Chun (Cell and Tissue Research, 2005)